COMPARISON OF MANUAL AND SEMIAUTOMATED FUNDUS AUTOFLUORESCENCE ANALYSIS OF MACULAR ATROPHY IN STARGARDT DISEASE PHENOTYPE. Issue 6 (June 2016) - Kuehlewein, Laura; Hariri, Amir H.; Ho, Alexander; Dustin, Laurie; Wolfson, Yulia; Strauss, Rupert W.; Scholl, Hendrik P. N.; Sadda, SriniVas R.
Abstract : Purpose: To evaluate manual and semiautomated grading techniques for assessing decreased fundus autofluorescence (DAF) in patients with Stargardt disease phenotype. Methods: Certified reading center graders performed manual and semiautomated (region finder—based) grading of confocal scanning laser ophthalmoscopy (cSLO) fundus autofluorescence (FAF) images for 41 eyes of 22 patients. Lesion types were defined based on the black level and sharpness of the border: definite decreased autofluorescence (DDAF), well, and poorly demarcated questionably decreased autofluorescence (WDQDAF, PDQDAF). Agreement in grading between the two methods and inter- and intra-grader agreement was assessed by kappa coefficients (κ) and intraclass correlation coefficients (ICC). Results: The mean ± standard deviation (SD) area was 3.07 ± 3.02 mm 2 for DDAF (n = 31), 1.53 ± 1.52 mm 2 for WDQDAF (n = 9), and 6.94 ± 10.06 mm 2 for PDQDAF (n = 17). The mean ± SD absolute difference in area between manual and semiautomated grading was 0.26 ± 0.28 mm 2 for DDAF, 0.20 ± 0.26 mm 2 for WDQDAF, and 4.05 ± 8.32 mm 2 for PDQDAF. The ICC (95% confidence interval) for method comparison was 0.992 (0.984–0.996) for DDAF, 0.976 (0.922–0.993) for WDQDAF, and 0.648 (0.306–0.842) for PDQDAF. Inter- and intra-grader agreement in manual and semiautomated quantitative grading was better for DDAF (0.981–0.996) and WDQDAF (0.995–0.999) than for PDQDAF (0.715–0.993). Conclusion: Manual and semiautomated grading methods showed similar levels of reproducibility for assessing areas of decreased autofluorescence in patients with Stargardt disease phenotype. Excellent agreement and reproducibility were observed for well demarcated lesions. Abstract : Manual and semiautomated grading methods show similar levels of reproducibility for assessing areas of decreased autofluorescence in patients with Stargardt disease phenotype.